Glass ceramic as well as preparation method and application thereof
By regulating the composition distribution ratio of microcrystalline glass, the crystallization of forsterilite crystal phase is promoted, and the mechanical properties and transmittance of existing microcrystalline glass are solved, and the comprehensive performance improvement of high transmittance, low coloring, high Young's modulus and high Vickers hardness is achieved.
Patent Information
- Application Number
- CN202311242991.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
AI Technical Summary
Existing microcrystalline glasses have shortcomings in both high transmittance, low coloring, high Young's modulus and high Vickers hardness, which limit their application in the field of electronic equipment.
By reasonably regulating the composition distribution ratio of microcrystalline glass, especially the control of high MgO content and types and content of alkali metal oxides, the crystallization of high hardness forsteroid crystal phase is promoted, and the mechanical properties and ion exchange capacity of the glass are improved.
The high transmittance, low coloring, high Young's modulus and high Vickers hardness of microcrystalline glass have been achieved, which has significantly improved its application performance in the field of electronic equipment.
Smart Images

Figure CN119683858A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of microcrystalline glass preparation, and in particular to a microcrystalline glass and a preparation method and application thereof. Background Art
[0002] As electronic devices such as smartphones and tablets develop towards larger sizes and ultra-thinness, higher requirements are placed on the mechanical properties of protective glass for electronic devices. Compared with the high-aluminum glass used in traditional mobile phone glass cover plates, microcrystalline glass combines the microcrystallization characteristics of glass and the dual effects of ion exchange, and its mechanical properties can be further improved. However, microcrystalline glass with excellent mechanical properties usually faces problems such as low transmittance and easy coloring, which limits its application in the field of glass cover plates. Therefore, it is necessary to develop a microcrystalline glass that has high transmittance, low coloring, and high ion exchange capacity. Summary of the invention
[0003] In view of this, an embodiment of the present application provides a microcrystalline glass, which has the characteristics of low coloration, high transmittance, high Young's modulus and high Vickers hardness, and can undergo efficient ion exchange chemical strengthening, so as to better meet the application needs in the field of electronic equipment.
[0004] Specifically, a first aspect of the embodiment of the present application provides a glass-ceramic, wherein the components of the glass-ceramic include, in molar percentage:
[0005] SiO 2 : 35%-52%;
[0006] Al 2 O 3 : 5%-15%;
[0007] Li 2 O: 2%-10%;
[0008] Na 2 O: 0%-6%;
[0009] K 2 O: 0%-15%;
[0010] Cs 2 O: 0%-11%;
[0011] MgO: 23%-38%;
[0012] TiO 2 : 1%-6%;
[0013] ZrO 2 : 0-4%;
[0014] ZnO: 0-8%;
[0015] CaO: 0-3%;
[0016] BaO: 0-2%;
[0017] GeO 2 : 0-5%;
[0018] B 2 O 3 : 0%-6%;
[0019] Among them, Na 2 O+K 2 O+Cs 2 O>0; the crystal phase in the microcrystalline glass includes a forsterite crystal phase, and the microcrystalline glass is transparent in the visible light band.
[0020] The glass-ceramics provided in the embodiments of the present application can effectively promote the high hardness forsterite crystal phase (Mg 2 SiO 4 ) by crystallization, so that the strength of the glass is improved, while it will not excessively affect the optical transmittance of the microcrystalline glass, which can still be transparent in the visible light band; and the ion exchange capacity of the microcrystalline glass is also significantly improved, so that the strength of the glass can be enhanced secondary, thereby facilitating the application of the microcrystalline glass in the field of electronic equipment.
[0021] In the embodiment of the present application, the microcrystalline glass does not contain Cr element. The microcrystalline glass of the present application that does not contain Cr element has no obvious absorption in the visible light band and has low coloring, which is conducive to its use as protective glass for electronic devices.
[0022] In the embodiment of the present application, the crystal phase in the microcrystalline glass does not contain TiO 2 Crystal. Glass component TiO 2 No TiO is formed 2 Crystals, which makes the microcrystalline glass have high transmittance in the visible light region and low coloration.
[0023] In some embodiments of the present application, the Cs 2 The molar percentage of O is 0.1%-10%. 2 O can reduce Mg 2 SiO 4 The effect of grain agglomeration and reducing the refractive index difference between the glass phase and the crystal phase in the microcrystalline glass makes its transmittance higher.
[0024] In some embodiments of the present application, the Na 2 The mole percentage of O is 0-2.9%.
[0025] In some embodiments of the present application, the molar percentage of MgO is 30.5%-38%. A moderately high MgO content can ensure that the microcrystalline glass has a moderate amount of high hardness Mg. 2 SiO 4 Crystals, and combined with the control of the content of alkali metal oxides, make the microcrystalline glass transparent in the visible light band.
[0026] In some embodiments of the present application, 5%≤Li 2 O+Na 2 O+K 2 O+Cs 2 O≤18%. Controlling the total molar content of alkali metal oxides in the microcrystalline glass within this range is more conducive to the precipitation of Mg with smaller grains and uniform distribution in the microcrystalline glass. 2 SiO 4 Crystalline, and has good glass forming ability and stability.
[0027] In the implementation mode of the present application, 0.4≤Al 2 O 3 / (Li 2 O+Na 2 O+K 2 O+Cs 2 O)≤1.4. This is beneficial to Mg 2 SiO 4 Crystals are smoothly precipitated in the microcrystalline glass, and the microcrystalline glass has good ion exchange capacity.
[0028] In the implementation mode of the present application, 0.5≤(MgO+Li 2 O+Na 2 O+K 2 O+Cs 2 O) / (SiO 2 +Al 2 O 3 )≤1.2. This can ensure the smooth precipitation of Mg in the microcrystalline glass 2 SiO 4 It is a crystal with a sufficiently high ion exchange capacity without affecting the network structure and light transmittance of the glass too much.
[0029] In the embodiment of the present application, the grain size of the forsterite crystal phase is less than or equal to 100 nm. The grain size of the forsterite crystal phase is relatively small, which is conducive to ensuring a high transmittance of the microcrystalline glass.
[0030] In the embodiment of the present application, when the thickness of the microcrystalline glass is ≤1 mm, the transmittance of the light with a wavelength of 550 nm is ≥88%, the haze in the visible light region is ≤0.2%, and the B value in the LAB three-dimensional color space satisfies: |B value|≤0.8. These parameters can reflect that the optical properties of the microcrystalline glass are good (high transmittance and low coloring), and it can be used in display glass cover plates and camera protection cover plates to better meet the optical requirements of display and shooting.
[0031] In the embodiment of the present application, the Young's modulus of the microcrystalline glass is ≥100 GPa. The microcrystalline glass has a relatively high Young's modulus and can better resist deformation.
[0032] In the embodiment of the present application, the Vickers hardness of the microcrystalline glass is ≥800kgf / mm 2 The microcrystalline glass has a high Vickers hardness and good impact resistance, and its Vickers hardness can be further improved after ion exchange strengthening.
[0033] A second aspect of the present application provides a method for preparing glass-ceramics, comprising:
[0034] The raw materials corresponding to the components of the microcrystalline glass are mixed according to the component ratio of the microcrystalline glass, and after melting, forming and annealing, a glass raw material is obtained; wherein, in terms of molar percentage, the components of the microcrystalline glass include:
[0035] SiO 2 : 35%-52%;
[0036] Al 2 O 3 : 5%-15%;
[0037] Li 2 O: 2%-10%;
[0038] Na 2 O: 0%-6%;
[0039] K 2 O: 0%-15%;
[0040] Cs 2 O: 0%-11%;
[0041] MgO: 27%-38%;
[0042] TiO 2 : 1%-6%;
[0043] ZrO 2 : 0-4%;
[0044] ZnO: 0-8%;
[0045] CaO: 0-3%;
[0046] BaO: 0-2%;
[0047] GeO 2 : 0-5%;
[0048] B 2 O 3 : 0%-6%;
[0049] Among them, Na 2 O+K 2 O+Cs 2 O>0;
[0050] The glass raw material is heat-treated to crystallize the glass raw material to obtain glass-ceramics; wherein the crystal phase in the glass-ceramics includes a forsterite crystal phase, and the glass-ceramics is transparent in the visible light band.
[0051] The above-mentioned preparation method of microcrystalline glass has a simple process and is suitable for industrial production. Microcrystalline glass with excellent comprehensive performance can be obtained by the preparation method.
[0052] A third aspect of an embodiment of the present application provides a strengthened microcrystalline glass, which includes a main body layer and a strengthening layer located on the surface of the main body layer, and the main body layer includes microcrystalline glass described in the first aspect of the embodiment of the present application, or microcrystalline glass prepared by the preparation method of microcrystalline glass described in the second aspect.
[0053] A fourth aspect of the embodiments of the present application provides a strengthened microcrystalline glass, which can be obtained by ion exchange of the microcrystalline glass described in the first aspect of the embodiments of the present application.
[0054] In the embodiment of the present application, the depth of the strengthening layer of the above-mentioned strengthened microcrystalline glass is greater than or equal to 100 μm. A larger strengthening layer depth can ensure that the strengthened microcrystalline glass has excellent anti-drop performance and improve the reliability of electronic devices using it.
[0055] In the embodiment of the present application, the surface compressive stress of the above-mentioned strengthened microcrystalline glass is greater than or equal to 220 MPa.
[0056] In the embodiment of the present application, the compressive stress CS_50 of the strengthened glass-ceramics at a depth of 50 μm in the strengthening layer is greater than or equal to 100 MPa. A higher CS_50 value can ensure that the strengthened glass-ceramics has a higher strength.
[0057] In the embodiment of the present application, the Vickers hardness of the tempered glass-ceramics is greater than or equal to 850 kgf / mm 2Compared with glass-ceramics without ion exchange, the Vickers hardness of the strengthened glass-ceramics is significantly improved, which can more effectively inhibit the expansion of cracks in it and improve its impact resistance and drop resistance.
[0058] The embodiment of the present application further provides a glass cover plate, which is made of the microcrystalline glass described in the first aspect of the embodiment of the present application, or made of the microcrystalline glass prepared by the method for preparing microcrystalline glass described in the second aspect, or made of the strengthened microcrystalline glass described in the third aspect or the fourth aspect of the embodiment of the present application. The glass cover plate can be a display cover plate, a back cover, or a camera protection cover plate of an electronic device.
[0059] An embodiment of the present application also provides an electronic device, including a shell assembled on the outside of the electronic device, and a circuit board located inside the shell, the shell is made of glass, and the glass includes the microcrystalline glass described in the first aspect of the embodiment of the present application, or the microcrystalline glass prepared by the preparation method of the microcrystalline glass described in the second aspect, or the strengthened microcrystalline glass described in the third aspect or fourth aspect of the embodiment of the present application.
[0060] In some embodiments of the present application, the housing includes a display screen cover assembled on the front side of the electronic device, and a back cover assembled on the back side of the electronic device; wherein the display screen cover and / or the back cover are made of the glass. In some other embodiments of the present application, the electronic device also includes a camera assembly located inside the housing, and the housing includes a camera protection cover, which is provided on the camera assembly, wherein the camera protection cover is made of the glass. The electronic device in the present application may be a display screen cover, a back cover, a camera protection cover, or one or more of which are made of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 A schematic diagram of the front structure of an electronic device provided in an embodiment of the present application.
[0062] Figure 2 A schematic diagram of the rear structure of an electronic device provided in an embodiment of the present application.
[0063] Figure 3 This is a schematic diagram of the structure of the chemically strengthened glass-ceramics provided in an embodiment of the present application.
[0064] Figure 4 This is the X-ray diffraction pattern of the glass-ceramics in Example 1 of the present invention.
[0065] Figure 5 This is the transmittance curve of the microcrystalline glass in Example 6 of the present application.
[0066] Figure 6This is a scanning electron microscope image of the glass-ceramics of Example 6 of the present application.
[0067] Figure 7 This is a transmission electron microscope photograph of the microcrystalline glass of Example 6 of the present application.
[0068] Figure 8 This is a stress curve diagram of ion exchange of the microcrystalline glass in Example 6 of the present application.
[0069] Fig. 9 This is the transmittance curve of the microcrystalline glass of comparative example 1.
[0070] Fig.10 The transmittance curve of the microcrystalline glass is analyzed for comparative example 4. DETAILED DESCRIPTION
[0071] The embodiments of the present application are described below in conjunction with the drawings in the embodiments of the present application.
[0072] See also Figure 1 and Figure 2 , an embodiment of the present application provides an electronic device 100, which can be a mobile phone, a tablet computer, a smart wearable device or other electronic product, and the electronic device 100 includes a shell assembled on the outside of the electronic device, and a circuit board located inside the shell. The shell includes a display cover 101 assembled on the front side of the electronic device 100 and a back cover 102 assembled on the back side of the electronic device 100, and the display cover 101 is covered on the display module, wherein the display cover 101 and / or the back cover 102 can be made of strengthened microcrystalline glass. The display cover 101 can be made entirely of strengthened microcrystalline glass, or only partially of strengthened microcrystalline glass; the back cover 102 can be made entirely of strengthened microcrystalline glass, or only partially of strengthened microcrystalline glass. In the embodiment of the present application, the display screen can be a touch display screen, and the display cover 101 can be a protective cover provided on the touch display screen. In the embodiment of the present application, the back cover 102 may cover only the back side (and the side away from the display screen) of the electronic device 100, or may cover both the back side and the side frame of the electronic device 100. Optionally, the back cover 102 may cover all the side frames around the electronic device, or may cover part of the side frames.
[0073] In some implementation modes of the present application, Figure 2As shown, the electronic device 100 also includes a camera assembly 2 located inside the housing, and the housing may include a camera protection cover 103, which is covered on the camera assembly 2 to protect the camera assembly 2, and the camera protection cover 103 is made of reinforced microcrystalline glass. In the embodiment of the present application, the camera protection cover 103 may be partially made of reinforced microcrystalline glass, or it may be made of reinforced microcrystalline glass in its entirety. In the embodiment of the present application, the setting position of the camera protection cover 103 is determined according to the setting position of the camera assembly 2, and it may be located on the front side of the electronic device 100, or it may be located on the back side of the electronic device 100. In some embodiments of the present application, the camera protection cover 103 may be a separate structure from the display screen cover 101 or the back cover 102. In other embodiments of the present application, the camera protection cover 103 may also be an integrated structure with the display screen cover 101 or the back cover 102.
[0074] In the embodiment of the present application, in the electronic device 100, any one, any two, or all three of the display screen cover 101, the back cover 102, and the camera protection cover 103 can be made of strengthened microcrystalline glass. Among them, the strengthened microcrystalline glass can be obtained by chemically strengthening microcrystalline glass by ion exchange.
[0075] At present, various protective glasses used in the electronic device 100, such as the display cover 101, the back cover 102, and the camera protection cover 103, are still mainly high-aluminum glass. Although its strength can be improved through ion exchange, its brittleness is still large and its drop resistance is poor. Compared with the commonly used high-aluminum glass, microcrystalline glass has more excellent mechanical properties and has received widespread attention in the industry. However, it is difficult for existing microcrystalline glass to have the characteristics of low coloration, high transmittance, high Young's modulus, and high Vickers hardness at the same time. For this reason, the embodiment of the present application provides a microcrystalline glass, which can have the characteristics of high transmittance, low coloration, high Young's modulus and high Vickers hardness. The microcrystalline glass or the strengthened microcrystalline glass obtained after strengthening can be used to make various protective glasses in the electronic device 100. Specifically, any one, or any two, or all three of the display cover 101, the back cover 102, and the camera protection cover 103 in the electronic device 100 may adopt the tempered microcrystalline glass provided in the embodiment of the present application to better meet the optical requirements of electronic device display and shooting, while improving the product reliability of the electronic device.
[0076] In the embodiment of the present application, the thickness of the strengthened microcrystalline glass used as the display cover 101, the back cover 102, and the camera protection cover 103 can be 0.4 mm-2 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, etc. In addition, the strengthened microcrystalline glass can be formed into 2D, 2.5D flat products, and can also be formed into 3D curved products.
[0077] Specifically, the glass-ceramics provided in the embodiments of the present application include the following components in molar percentage:
[0078] SiO 2 : 35%-52%;
[0079] Al 2 O 3 : 5%-15%;
[0080] Li 2 O: 2%-10%;
[0081] Na 2 O: 0%-6%;
[0082] K 2 O: 0%-15%;
[0083] Cs 2 O: 0%-11%;
[0084] MgO: 27%-38%;
[0085] TiO 2 : 1%-6%;
[0086] ZrO 2 : 0-4%;
[0087] ZnO: 0-8%;
[0088] CaO: 0-3%;
[0089] BaO: 0-2%;
[0090] GeO 2 : 0-5%;
[0091] B 2 O 3 : 0%-6%;
[0092] Among them, Na 2 O+K 2 O+Cs 2 O>0; the crystal phase in the microcrystalline glass includes a forsterite crystal phase, and the microcrystalline glass is transparent in the visible light band.
[0093] The microcrystalline glass provided in the embodiment of the present application is obtained by reasonably adjusting the molar ratio of each oxide in the glass component, especially controlling the high MgO content and the alkali metal oxide (Li 2 O、Na 2 O.K 2 O、Cs 2 O) can realize the controlled precipitation of high hardness forsterite crystal phase (Mg 2 SiO 4 ), so that the glass is microcrystallized, and the mechanical properties such as hardness and scratch resistance of the glass are improved; the content of alkali metal oxides in the glass components is reasonably controlled, and the microcrystalline glass can also be efficiently ion exchanged, and a deeper strengthening layer depth and a higher surface compressive stress are obtained, so that the strength of the microcrystalline glass is secondary enhanced, and finally excellent mechanical properties such as anti-drop and anti-scratch performance are obtained; in addition, while the microcrystalline glass has good mechanical properties, it can still remain transparent in the visible light band, which is conducive to its application in the field of electronic equipment. Therefore, the microcrystalline glass provided in the embodiment of the present application can better combine high transmittance, low coloring, and excellent mechanical properties (high Young's modulus, high Vickers hardness), so as to better meet the application needs of protective glass materials in the fields of electronic equipment and so on.
[0094] The term "ion exchange" in this application is commonly referred to as "chemical strengthening". Its main principle is to exchange the larger ions (such as K + 、Na + ) and ions with smaller radius in glass (such as Na + , Li + Through the "crowding effect", an ion exchange layer with a certain depth (also known as a strengthening layer, or a compressive stress layer, etc.) is formed on the glass surface.
[0095] In the embodiment of the present application, the microcrystalline glass does not contain Cr element. That is, the microcrystalline glass of the present application does not contain Cr 2 O 3 ,Cr 2 O 3 The molar percentage in the microcrystalline glass is 0%. The microcrystalline glass of the present application that does not contain Cr element has no obvious absorption in the visible light band, has low coloration and high transparency, which is conducive to its use as protective glass for electronic equipment.
[0096] In the embodiment of the present application, the crystal phase in the microcrystalline glass does not contain TiO 2 Crystal. That is, the glass component TiO 2 No TiO is formed 2 Crystal, but Ti 4+ions to form Ti-containing crystal nuclei, promoting Mg 2 SiO 4 Crystallization of crystals. Does not contain TiO 2 The crystal glass-ceramics has high transmittance in the visible light region and low coloration, being almost colorless in the visible light band.
[0097] In this application, SiO 2 (Silicon dioxide) is the main component of the glass network structure and also the Mg 2 SiO 4 The content of the components necessary for crystallization not only affects the structural stability of the glass, but also affects the Mg 2 SiO 4 The applicant has found through extensive research that Mg 2 SiO 4 The crystallization is closely related to the connection degree of the glass network. The lower the connection degree of the glass network, that is, the looser the glass network structure, the easier it is to promote the crystallization of Mg. 2 SiO 4 The looser the network structure, the more Mg 2 SiO 4 The smaller the grain size, the higher the transmittance of the microcrystalline glass. 2 The content of SiO should not be too high. 2 When the content is too high, it will not only lead to high viscosity of the glass melt and high melting cost, but also inhibit the Mg 2 SiO 4 The crystallization of Mg 2 SiO 4 The grain size of SiO is large, which reduces the transmittance of glass-ceramics. 2 The content of SiO 2 Too low a content will result in a lower degree of connection of the glass network structure, a lower glass forming effect, and a lower glass stability. 2 The molar percentage of SiO is controlled between 35% and 52%. 2 The molar percentage is specifically 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 49.5%, 50%, 51% or 52%, etc. In some embodiments of the present application, SiO 2 The molar percentage may be 35%-49%, and further may be 36.5%-48%.
[0098] In this application, Al 2 O 3(Aluminum oxide) is a network intermediate oxide in glass. Al 2 O 3 They play different roles in different glass environments. When alkali metal ions (Li + , K + 、Na + , Cs + ) and alkaline earth metal ions (Mg 2+ , Ca 2+ , Ba 2+ ) is greater than the total molar content of Al 2 O 3 When 3+ All are four-coordinated. At this time, Al 2 O 3 As a network former, [AlO 4 ] tetrahedron participates in the glass network structure. When the total molar content of alkali metal ions and alkaline earth metal ions in the glass is less than Al 2 O 3 When part of Al 3+ For penta- or hexa-coordinated, Al 2 O 3 It is a network modified body. In this application, Al 2 O 3 It not only affects the network connectivity of the glass, but also affects the Mg 2 SiO 4 The crystallization performance of the glass-ceramics also affects the ion exchange capacity. 2 O 3 The higher the content of Al, the higher the network connection degree of the glass, the higher the stability and mechanical properties of the glass, but 2 O 3 If the content of Mg is too high, although the stability of the glass network structure increases, the melting of the glass becomes difficult; in addition, the denser the glass network structure, the more Mg 2 SiO 4 The more difficult the crystallization is, therefore, in this application, Al 2 O 3 The content of [AlO 4 ]The volume ratio of tetrahedron [SiO 4 ] The tetrahedron is large, which can increase the network gap, making it easier for the alkali metal ions involved in ion exchange to move, and the ion exchange performance is improved. 2 O 3 The content of Al should not be too low. 2 O 3 The molar percentage of Al is controlled between 5% and 15%.2 O 3 The molar percentage of Al may be 5.5%, 6%, 6.5%, 7%, 8%, 9%, 9.5%, 9.8%, 10%, 11%, 12%, 13%, 14%, 15%, etc. In some embodiments of the present application, Al 2 O 3 The molar percentage of Al is 5%-14%, and further can be 5%-10%. In some embodiments, Al 2 O 3 The molar percentage is 6%-9.8%.
[0099] In this application, Li 2 O (lithium oxide) is a network modifier in glass, which can destroy the network structure of glass. Its content can affect the degree of connection of glass network structure, thus affecting Mg 2 SiO 4 The crystallization performance of Li 2 O is the main component involved in ion exchange when glass-ceramics is strengthened, and its content also affects the ion exchange performance of the glass. 2 As the O content increases, the glass network structure becomes looser, which is more conducive to the formation of Mg with smaller particle size. 2 SiO 4 Crystal precipitation, the transmittance of microcrystalline glass is high, and Li 2 O also has the effect of lowering the melting point of glass. The higher its content, the easier it is to melt the glass. 2 The higher the O content, the better the ion exchange performance of the glass, the deeper the ion exchange layer, and the more obvious the improvement in the strength of the glass. 2 O can easily lead to unstable structure of glass, poor glass forming property and difficult molding. 2 The molar percentage of O is controlled between 2% and 10%. 2 The molar percentage of O can be 2.5%, 3%, 4%, 5%, 5.5%, 6%, 6.5%, 7%, 8%, 9%, 9.5%, etc.
[0100] Na 2 O is a network modifier in glass and its role is similar to that of Li 2 O is similar to ion exchange. + The electronegativity is less than that of Li + , electron-donating ability is stronger than Li + , the metallic property is stronger, some Na 2 O vs Li 2 After O substitution, Mg 2 SiO 4The size of the crystal, the transmittance of glass-ceramics is higher; but Na 2 When the O content is too high, the network structure of the glass is unstable and the glass is difficult to form. 2 The molar percentage of O is controlled between 0 and 6%. 2 The mole percentage of O can be 0, 0.1%, 0.2%, 0.5%, 1%, 1.2%, 1.5%, 2%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, etc. In some examples, Na 2 The mole percentage of O is 0-2.9%.
[0101] K 2 O is a network modifier in the glass, K + The field strength is lower than Na + and Li + . K + The introduction of can reduce the connectivity of the glass network structure and reduce the Mg 2 SiO 4 The grain size increases the transmittance of the glass, but K + Too high a content will lead to a looser glass network structure, reduced glass-forming properties, increased crystallization tendency, and difficulty in obtaining transparent glass raw materials. Therefore, considering all aspects, this application will use K 2 The content of O is controlled at 0-15%.
[0102] Cs 2 O is a network modifier in the glass, where Cs + It has weaker electronegativity and stronger electron-donating ability. Its role is similar to that of K + Similar, Cs + The introduction of 2 SiO 4 The grain size of Cs increases the transmittance of the glass. + The introduction of Cs can also effectively weaken the phase separation formed by Mg enrichment in the glass, reduce the clustering between grains, and 2 The introduction of O can also increase the refractive index of the glass matrix, reduce the refractive index difference between the glass phase and the crystalline phase, and thus increase the transmittance of the microcrystalline glass. 2 The content of O does not exceed 11%. In some embodiments, Cs 2 The molar percentage of O is 0.1%-10%. The lower content of Cs 2 O can reduce Mg 2 SiO 4The effect of grain agglomeration and reducing the refractive index difference between the glass phase and the crystal phase in the microcrystalline glass. 2 The molar percentage of O can be specifically 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 1.0%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 4.0%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 8.5%, 9.0%, 9.5%, 9.8%, etc. In some embodiments, Cs 2 The molar percentage of O is 0.1%-3%. Lower Cs 2 O can effectively improve the light transmittance of microcrystalline glass.
[0103] Na 2 O (sodium oxide), K 2 O (potassium oxide), Cs 2 O (cesium oxide) is also a network modifier in glass. The microcrystalline glass of the present application contains an appropriate amount of Li 2 O, so as to ensure that the microcrystalline glass has a deeper ion exchange depth and obtains a higher surface stress after exchange, and the microcrystalline glass also includes Na 2 O.K 2 O、Cs 2 O (the sum of the molar proportions of the three is greater than 0), so that the introduction of Li 2 O as an alkali metal oxide brings about poor glass forming properties (manifested in the glass melt being easily devitrified when cooled) and the glass-ceramics being easily opaque after heat treatment, so that the glass has both efficient ion exchange capacity and high transmittance. In some embodiments of the present application, Na 2 O+K 2 O+Cs 2 O ≥ 2.9%, to ensure that the total content of alkali metal oxides in the system is not too low, to ensure that Mg 2 SiO 4 It is easy to crystallize, and the crystal size is small and the light transmittance is high.
[0104] In some embodiments of the present application, the total amount of alkali metal oxides R 2 O(R 2 O=Li 2 O+Na 2 O+K 2 O+Cs 2 O) is in the range of 5%-18%. This ensures that there is sufficient R 2 O can make Mg 2 SiO 4 The smooth crystallization of Mg 2SiO 4 The grain size is small, and too high R 2 O leads to reduced glass stability, difficulty in glass molding, and reduced glass transmittance. 2 The O content may specifically be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, etc.
[0105] In order to better ensure the Mg content in glass-ceramics 2 SiO 4 The crystals are smoothly precipitated and have good ion exchange capacity. In some embodiments of the present application, 0.4≤Al 2 O 3 / R 2 O≤1.4. That is Al 2 O 3 The molar percentage of R 2 The molar percentage ratio of O is 0.4-1.4, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc. In some embodiments, Al 2 O 3 / R 2 O is in the range of 0.5-1.2.
[0106] In this application, MgO (magnesium oxide) is Mg 2 SiO 4 The amount of oxides necessary for crystallization directly affects the Mg 2 SiO 4 The higher the MgO content, the higher the Mg 2 SiO 4 The easier it is to crystallize, but if the MgO content is too high, the stability and glass-forming properties of the glass will deteriorate, and glass molding will be difficult. 2 SiO 4 Not easy to crystallize, and has Mg 2 SiO 4When precipitated, its grains are larger and the transmittance of the microcrystalline glass is lower. After comprehensive consideration, the embodiment of the present application controls the molar percentage of MgO between 27% and 38%. Specifically, the molar percentage of MgO can be 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, etc. In some embodiments of the present application, the molar percentage of MgO is 30.5%-38%. A moderately high MgO content can ensure that the microcrystalline glass has a moderate amount of high-hardness Mg. 2 SiO 4 Crystals, and combined with the control of the content of alkali metal oxides, the glass maintains a high visible light transmittance.
[0107] In order to better ensure the smooth precipitation of Mg in glass-ceramics 2 SiO 4 Crystals, and have a sufficiently high ion exchange capacity, and do not affect the network structure and light transmittance of the glass too much. In some embodiments of the present application, control: 0.5≤(MgO+R 2 O) / (SiO 2 +Al 2 O 3 )≤1.2. Specifically, the ratio may be 0.55, 0.6, 0.65, 0.7, 0.8, 0.9, 1.0, 1.1, etc.
[0108] In this application, TiO 2 (TiO2) acts as a nucleating agent in glass-ceramics and can promote the crystallization of Mg in the process of forming glass-ceramics. 2 SiO 4 Crystals precipitate in a glass matrix. TiO 2 The content of TiO should not be too high, otherwise it will not only affect the stability of the glass, but also color the glass, causing the glass to absorb visible light and reduce the transmittance of the microcrystalline glass; TiO 2 The content of Mg should not be too low, otherwise the nucleation effect will be poor and the precipitated Mg 2 SiO 4 The larger the grain size, the greater the scattering of visible light, and the lower the transmittance of the microcrystalline glass. 2 The prepared microcrystalline glass is almost colorless and transparent, and has a high transmittance in the visible light band. 2 The molar percentage is in the range of 1%-6% to ensure that the Mg2 SiO 4 Crystalline glass is almost colorless and transparent, and has a high transmittance in the visible light band. 2 The molar percentage of TiO can be 1.5%, 2%, 2.5%, 3%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 5%, 5.5%, etc. In some embodiments, TiO 2 The molar percentage is 1%-4.5%.
[0109] ZrO 2 (Zirconium oxide) can also act as a nucleating agent, which can react with TiO 2 Use together, appropriately introduce ZrO 2 It is beneficial to improve the glass nucleation performance. 2 The melting point is high and the solubility in aluminosilicate is low. Therefore, ZrO 2 The content of ZrO should not be too high. After comprehensive consideration, the present embodiment controls 2 The molar percentage of ZrO is in the range of 0-4%. 2 The mole percentage can be 0, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, etc.
[0110] ZnO (zinc oxide) can be used as an intermediate oxide in glass. The introduction of ZnO can improve the melting properties of glass, reduce the crystallization temperature of glass, and promote the 2 SiO 4 However, too high a ZnO content will reduce the stability of the glass and cause the glass to lose clarity. Taking the above effects into consideration, the molar percentage of ZnO in the embodiment of the present application is controlled between 0-8%, for example, 0, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc.
[0111] In some cases, the above-mentioned microcrystalline glass of the present application may also contain a certain amount of CaO (calcium oxide) and BaO (barium oxide), the main function of which is to improve the crystallization performance of the glass and inhibit the Mg 2 SiO 4 The molar percentages of CaO and BaO in the present embodiment are not more than 3% and 2% respectively. 2 SiO 4 When the grains are smaller, it is also beneficial for other properties of the glass to be maintained at a higher level.
[0112] In some cases, the above-mentioned glass-ceramics of the present application may contain a certain amount of GeO 2. Due to Mg 2 SiO 4 The refractive index of the crystal is higher than that of the glass matrix, and the high refractive index GeO 2 It can increase the refractive index of the glass matrix, thereby reducing the Mg 2 SiO 4 The difference in refractive index between the crystal and the glass matrix reduces the scattering of visible light by the glass and increases the transmittance of the microcrystalline glass. However, too much GeO 2 This leads to an unstable structure of the glass and an increased tendency of crystallization of the glass. 2 The molar percentage does not exceed 5%, for example 0, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.9%, etc.
[0113] B 2 O 3 It can be used as a flux in the glass formation process to introduce B 2 O 3 It can improve the melting viscosity of glass and inhibit Mg 2 SiO 4 Excessive growth of crystals increases the transmittance of microcrystalline glass; but too much B 2 O 3 This will cause the glass to separate into phases and the glass forming properties to deteriorate. Taking the above effects into consideration, the embodiment of the present application reduces the B 2 O 3 The molar percentage is controlled in the range of 0-6%, for example, 0, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2.0%, 2.5%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 5.8% and the like.
[0114] In some embodiments of the present application, the microcrystalline glass may further include a clarifier. The addition of the clarifier can reduce bubbles, streaks, etc. in the glass melt during the glass melting process, thereby achieving a better melting effect. 2 O 3 (antimony trioxide), As 2 O 3 (arsenic oxide), SnO 2 (tin dioxide), Na 2 SO 4 (sodium sulfate), K 2 SO 4 (potassium sulfate), Li 2 SO 4 (Lithium sulfate), NaNO 3(sodium nitrate), Ba(NO 3 ) 2 (barium nitrate), CaF 2 (Calcium Fluoride), Na 2 SiF 6 (sodium fluorosilicate) or more thereof, but not limited thereto.
[0115] In the present application, Mg is used in the above-mentioned glass-ceramics. 2 SiO 4 As the main crystalline phase, Mg 2 SiO 4 The microcrystalline glass of the present application includes a crystal phase and a glass phase, wherein the crystal phase includes a forsterite crystal phase Mg 2 SiO 4 The glassy phase and uniformly distributed Mg 2 SiO 4 Together they form a dense structure of glass, and based on Mg 2 SiO 4 It has excellent mechanical properties, so that the microcrystalline glass can obtain higher hardness and Young's modulus, and can obtain good optical properties.
[0116] In the embodiment of the present application, the grain size of the forsterite crystal phase is less than or equal to 100 nm. 2 SiO 4 The grain size of the crystal is much smaller than the wavelength of visible light, and the scattering of visible light is small, which is conducive to the high transmittance of the microcrystalline glass. In some embodiments, the grain size of the forsterite crystal phase is ≤80nm, ≤70nm, ≤60nm, ≤50nm, ≤45nm, or ≤40nm, etc.
[0117] In the embodiment of the present application, the mass percentage of the forsterite crystalline phase in the microcrystalline glass is 10%-45%. That is, the crystallinity of the forsterite crystalline phase in the microcrystalline glass is 10%-45%. Regulating the crystallinity of the forsterite crystalline phase in this range can regulate the hardness, Young's modulus, light transmittance, etc. of the microcrystalline glass, and the comprehensive performance is relatively excellent. Specifically, the mass percentage of the forsterite crystalline phase in the microcrystalline glass can be 20%, 25%, 28%, 30%, 35%, 40%, 42%, 45%, etc. In some embodiments, the value is 28-40%. Among them, the crystalline phase content in the microcrystalline glass can be detected by X-ray diffraction.
[0118] In the implementation manner of the present application, the Young's modulus of the microcrystalline glass is ≥100GPa. Young's modulus is a physical quantity that describes the ability of a solid material to resist deformation. The larger the Young's modulus, the less likely the solid material is to deform under external force. The microcrystalline glass in the embodiment of the present application has a higher Young's modulus, which can better resist deformation, thereby helping to improve the drop resistance of electronic devices when the microcrystalline glass is applied to electronic devices. In some embodiments, the Young's modulus of the microcrystalline glass can be ≥104GPa, ≥105GPa, ≥110GPa, or even ≥115GPa.
[0119] In the embodiment of the present application, the Vickers hardness of the microcrystalline glass is ≥800kgf / mm 2 The microcrystalline glass has a high Vickers hardness, which can effectively inhibit the expansion of cracks in the microcrystalline glass and improve the impact resistance and drop resistance. In some embodiments, the Vickers hardness of the microcrystalline glass can be ≥850kgf / mm 2 ,≥860kgf / mm 2 , even ≥900kgf / mm 2 wait.
[0120] In the implementation manner of the present application, the above-mentioned microcrystalline glass has the above-mentioned crystal phase characteristics and mechanical properties while still having excellent optical properties. Specifically, when the thickness of the above-mentioned microcrystalline glass is ≤1.0mm, the transmittance at a wavelength of 550nm is ≥88%. In some embodiments, the transmittance is ≥89% or even ≥90%. 550nm is a typical wavelength in the visible light band, and the transmittance of 550nm light is relatively high, which can reflect that the microcrystalline glass of the embodiment of the present application has a high visible light transmittance, and when it is used for display glass cover plates and camera protection cover plates, it can better meet the optical requirements of display and shooting.
[0121] In the embodiment of the present application, when the thickness of the above-mentioned microcrystalline glass is ≤1.0mm, the haze in the visible light region is ≤0.2%. The lower haze can also reflect that the microcrystalline glass of the embodiment has a higher transmittance and no "frosting" phenomenon, and can better meet the optical requirements of display and shooting when it is used for display glass cover plates and camera protection cover plates. In some embodiments, the haze in the visible light region is ≤0.18%, or ≤0.15%, etc.
[0122] In the embodiment of the present application, when the thickness of the microcrystalline glass is ≤1.0 mm, its B value in the LAB three-dimensional color space satisfies: |B value|≤0.8. That is, the B value is between -0.8 and 0.8. This can reflect that the microcrystalline glass of the embodiment of the present application has low coloration and will not turn yellow or blue, which is conducive to ensuring that the transmittance of the microcrystalline glass is high. In some embodiments, |B value|≤0.5.
[0123] The present application also provides a method for preparing the above-mentioned glass-ceramics, comprising:
[0124] (1) Mixing raw materials corresponding to various components of the microcrystalline glass according to the component ratio of the microcrystalline glass, and obtaining glass raw materials after melting, forming, and annealing; wherein, in terms of molar percentage, the components of the microcrystalline glass include:
[0125] SiO 2 : 35%-52%;
[0126] Al 2 O 3 : 5%-15%;
[0127] Li 2 O: 2%-10%;
[0128] Na 2 O: 0%-6%;
[0129] K 2 O: 0%-15%;
[0130] Cs 2 O: 0%-11%;
[0131] MgO: 27%-38%;
[0132] TiO 2 : 1%-6%;
[0133] ZrO 2 : 0-4%;
[0134] ZnO: 0-8%;
[0135] CaO: 0-3%;
[0136] BaO: 0-2%;
[0137] GeO 2 : 0-5%;
[0138] B 2 O 3 : 0%-6%;
[0139] Among them, Na 2 O+K 2 O+Cs 2 O>0;
[0140] (2) heat-treating the glass raw material to crystallize the glass raw material to obtain microcrystalline glass; wherein the crystal phase in the microcrystalline glass includes a forsterite crystal phase, and the microcrystalline glass is transparent in the visible light band.
[0141] The embodiment of the present application can prepare microcrystalline glass with high transmittance, low coloring, high Young's modulus, high Vickers hardness, and high ion exchange capacity by regulating the suitable component ratio of glass raw materials and combining heat treatment to achieve crystallization, so as to meet the high performance requirements of glass products in fields such as electronic equipment.
[0142] Although the components in the aforementioned glass-ceramics are expressed on an oxide basis, in actual preparation, the raw materials corresponding to the components of the glass-ceramics can be various forms of materials available in the field of glass preparation. 2 Silica sand etc. can be used. 2 O 3 Can use wax stone, alumina, aluminum hydroxide etc., the above-mentioned Li 2 O can be made of Li 2 CO 3 , the aforementioned Na 2 O can be made of Na 2 CO 3 , the aforementioned TiO 2 The corresponding oxide materials can be directly used. The aforementioned MgO can be made of dolomite, basic magnesium carbonate, light magnesium oxide, etc. The aforementioned ZnO can be made of ZnO, zinc silicate, etc. The aforementioned ZrO 2 ZrO can be used 2 , zirconium silicate, etc., the aforementioned SiO 2 、Al 2 O 3 , Li 2 O, ZnO and MgO etc. can be added together in the form of aluminosilicate glass. The raw material forms corresponding to each glass component are not limited, as long as the proportions of these materials can meet the aforementioned oxide content requirements after being converted into oxides.
[0143] In step (1), the melting specifically refers to melting the raw materials corresponding to each component to form a glass melt. The melting temperature may be 1400°C-1650°C, such as 1420°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, etc. Generally, after the melting, a clarification and homogenization treatment is further performed to shape the uniformly mixed and clarified glass melt.
[0144] Wherein, the molding is the process of converting the melted glass into a geometrically shaped product (i.e., glass raw material) at a certain temperature. Wherein, the molding method may include but is not limited to casting molding, calendering molding, float molding, overflow molding, slit up / down drawing molding, etc. The purpose of annealing after molding is to reduce or eliminate the thermal stress generated in the glass as much as possible. In the embodiment of the present application, the annealing temperature may be 400°C-650°C, for example, 420°C, 450°C, 500°C, 550°C, 600°C, 620°C, etc. In some embodiments, the glass raw material is plate-shaped / block-shaped, and its thickness can be selected according to the application requirements. The glass raw material also does not contain a crystalline phase.
[0145] In step (2), the glass substrate obtained in step (1) is heat-treated to crystallize it, produce the expected crystal phase and glass phase, and obtain microcrystalline glass. After the glass components are determined, the crystal composition and performance of microcrystalline glass mainly depend on the heat treatment process. The heat treatment can be a one-step heat treatment or a two-step heat treatment. Wherein, when the heat treatment is a one-step heat treatment, the heat treatment temperature ranges from 640-900°C and the time is 2-20h. The heat treatment temperature can be, for example, 650°C, 680°C, 700°C, 720°C, 730°C, 750°C, 760°C, 780°C, 800°C, 820°C, 850°C, 860°C, 880°C, 890°C, etc.; the time can be 1h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, etc. Wherein, when the heat treatment is a two-step heat treatment, the first step heat treatment temperature is 600-660°C, and the time is 0.5-10h; the second step heat treatment temperature is 660-900°C, and the time is 1-20h. The first step heat treatment temperature is greater than the second step heat treatment temperature. Specifically, the first step heat treatment temperature can be 610°C, 620°C, 630°C, 640°C, 650°C, etc., and the time can be 0.5h, 1h, 2h, 5h, 6h, 8h, 10h, etc. The second step heat treatment temperature can be 660℃, 670℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 780℃, 790℃, 800℃, 820℃, 850℃, 860℃, 870℃, 880℃, 890℃, etc., and the time can be 1h, 2h, 5h, 6h, 8h, 10h, 12h, 15h, 18h, etc. Heat treatment is an important step to achieve crystallization of glass raw materials. The embodiment of the present application can better improve the crystallinity of microcrystalline glass by adopting a suitable heat treatment system to obtain Mg with a smaller grain size. 2 SiO 4 Crystal.
[0146] In step (2), the glass substrate obtained after the glass raw material is crystallized basically maintains its original morphology. In some embodiments of the present application, after the crystallization treatment, the microcrystalline glass can also be cold-processed to obtain a microcrystalline glass product in a sheet or other desired shape, so as to be subsequently subjected to chemical strengthening treatment. Among them, the microcrystalline glass product can be a 2D-shaped flat sheet, or a 2.5D-shaped, 3D-shaped, etc., which can be specifically adjusted according to actual design requirements.
[0147] The method for preparing the above-mentioned microcrystalline glass provided in the embodiment of the present application has a simple process and is suitable for industrial production.
[0148] The embodiment of the present application also provides a strengthened glass-ceramic, which can be obtained by ion exchange (i.e., chemical strengthening) of the glass-ceramic described above in the embodiment of the present application. After ion exchange, a strengthening layer (i.e., a compressive stress layer) of a certain depth is formed on the surface of the glass-ceramic, which has a higher surface compressive stress, and the mechanical properties are further improved, such as the surface hardness, fracture toughness and other properties become better, and the ability to resist external forces is greatly improved.
[0149] See also Figure 3 , Figure 3 A schematic diagram of the structure of the strengthened glass-ceramics provided in the embodiment of the present application. The strengthened glass-ceramics 10 includes a main layer 11 and a strengthening layer 12 located on the surface of the main layer 11. The main layer 11 is completely consistent with the glass-ceramics described above in the embodiment of the present application (including components and crystal composition, etc.), that is, the main layer 11 includes the glass-ceramics described above in the embodiment of the present application. The strengthening layer 12 can be regarded as the product of ion exchange of the main layer 11. After the ion exchange, the components or crystal composition of the strengthening layer 12 have undergone some changes relative to the main layer 11. The strengthening layer 12 can be formed on one side of the main layer 11, or on two opposite sides of the main layer 11.
[0150] In the embodiment of the present application, the depth DOL of the strengthening layer 12 of the strengthened microcrystalline glass 10 may be greater than or equal to 100 μm. The depth of the strengthening layer refers to the depth of the strengthening layer on a single side of the strengthened microcrystalline glass, that is, the distance from the surface of the strengthened glass to the position where the compressive stress value is 0 from the surface of the strengthened microcrystalline glass. The greater the depth of the strengthening layer, the better the drop resistance of the strengthened microcrystalline glass, which can better improve the reliability of electronic equipment. In some embodiments, the depth of the strengthening layer 12 is ≥105 μm, ≥110 μm, ≥115 μm, ≥120 μm, etc. In some embodiments, the depth of the strengthening layer 12 is between 105 μm and 120 μm.
[0151] In the embodiment of the present application, after ion exchange, the surface compressive stress of the strengthened microcrystalline glass can be greater than or equal to 220MPa. The higher surface compressive stress can make the strengthened microcrystalline glass have higher hardness and fracture toughness, so that the strengthened microcrystalline glass has excellent anti-drop performance.
[0152] In the embodiment of the present application, the compressive stress CS_50 of the strengthened glass-ceramics at a depth of 50 μm in the strengthening layer is ≥100 MPa. Among them, 50 μm is the depth value of the strengthening layer calculated from the surface of the strengthening layer 12, specifically the compressive stress value at a distance of 50 μm from the surface of the strengthening layer inside the strengthened glass-ceramics. A higher CS_50 value can ensure that the strengthened glass-ceramics has higher strength and better drop resistance. Specifically, the CS_50 can be 102MPa, 105MPa, 106MPa, 107MPa, 108MPa, 110MPa, 112MPa, 116MPa, 118MPa, 120MPa, 125MPa, 130MPa, etc.
[0153] After ion exchange, the Vickers hardness of the above-mentioned microcrystalline glass is significantly improved. In the embodiment of the present application, the Vickers hardness of the strengthened microcrystalline glass is ≥850kgf / mm 2 The strengthened microcrystalline glass has a higher Vickers hardness, which can effectively inhibit the propagation of cracks therein and improve its impact resistance and drop resistance. In some embodiments, the Vickers hardness of the strengthened microcrystalline glass is ≥860 kgf / mm 2 , ≥880kgf / mm 2 ,≥900kgf / mm 2 ,≥950kgf / mm 2 ,≥960kgf / mm 2 ,≥970kgf / mm 2 ,≥980kgf / mm 2 , even ≥990kgf / mm 2 wait.
[0154] After the microcrystalline glass is ion exchanged, the light transmittance of the obtained strengthened microcrystalline glass is almost unchanged compared with the aforementioned microcrystalline glass. The transmittance of the strengthened microcrystalline glass with a thickness of ≤1mm at a wavelength of 550nm is ≥88%; the haze in the visible light region is ≤0.2%; and the B value in the LAB three-dimensional color space is ≤0.8. The specific values of each parameter can be found in the description of the previous text of this application.
[0155] The strengthened microcrystalline glass is obtained by ion exchange of the microcrystalline glass in the embodiment of the present application, wherein the ion exchange may be a one-step ion exchange process or a two-step ion exchange process. The one-step ion exchange process is to place the microcrystalline glass in an ion exchange molten salt for one-step ion exchange. The ion exchange molten salt used in the one-step ion exchange process may include KNO 3 Molten salt, or NaNO 3 Molten salt, or KNO 3 and NaNO 3 The suitable ion exchange temperature may be 380-520°C, for example, 400, 420, 450, 480, 500 or 510°C, etc.; the time may be 0.5h-16h, for example, specifically 1h, 1.5h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, etc.
[0156] For the two-step ion exchange process, in some embodiments of the present application, the first ion exchange molten salt used in the first step of ion exchange can be pure NaNO 3 Molten salt, or KNO 3 and NaNO 3 The mixed molten salt is exchanged with Na + →Li + The second ion exchange molten salt used in the second step of ion exchange can be KNO 3 Molten salt, or KNO 3 and NaNO 3 The mixed molten salt is exchanged with K + →Na + The temperature of the first step ion exchange and the temperature of the second step ion exchange can be independently in the range of 380-520° C., and the sum of the time of the first step ion exchange and the second step ion exchange can be 1-32 hours.
[0157] The above-mentioned strengthened microcrystalline glass provided in the embodiment of the present application has high transmittance, low coloration and excellent mechanical properties, and can be used in various electronic devices, specifically as glass cover plates in electronic devices, to meet the optical requirements of electronic devices such as display and shooting, while improving product reliability. Specifically, electronic devices include but are not limited to mobile phones, tablet computers, desktop computers, laptop computers, smart screens, displays, speakers, glasses, watches, headphones, car-mounted products and other electronic terminal devices related to mobile office, smart home, sports health, audio and video entertainment and smart travel. Among them, the above-mentioned Figure 1-Figure 2 The application of the strengthened micro-ceramic glass in an electronic device 100 such as a mobile phone is exemplified.
[0158] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0159] The glass raw materials are prepared according to the composition listed in Table 1. After the raw materials are evenly mixed, they are melted at a temperature of 1400-1650° C. to obtain a homogenized and clarified molten glass. The molten glass is cast into a molding mold for molding, and annealed at 400-650° C. to obtain a bulk glass raw material. The glass substrate is transparent, colorless, and does not contain a crystalline phase.
[0160] The glass raw material obtained above is heat-treated to crystallize and obtain microcrystalline glass containing a crystalline phase; wherein the heat treatment adopts a two-step heat treatment method, the first step of heat treatment temperature is 600-660°C, and the time is 0.5-10h; the second step of heat treatment temperature is 660-900°C, and the time is 1-20h.
[0161] According to the desired shape and size requirements, the above-mentioned microcrystalline glass is cut, CNC, ground and cleaned to obtain a microcrystalline glass substrate of the desired shape (such as a sheet). After that, the microcrystalline glass substrate is immersed in an ion exchange molten salt for ion exchange to obtain a strengthened microcrystalline glass.
[0162] The heat treatment process used in Example 1 is as follows: the first step heat treatment temperature is 640°C, the time is 10 hours, and the second step heat treatment temperature is 680°C, the time is 4 hours. Example 1 uses a one-step ion exchange method for the microcrystalline glass, and the molten salt used is NaNO 3 , the ion exchange temperature is 480℃, and the ion exchange time is 8h.
[0163] The heat treatment process of Example 2 is a two-step method, in which the first step is at a temperature of 620°C for 8 hours, and the second step is at a temperature of 680°C for 4 hours. The ion exchange process is the same as that of Example 1.
[0164] The heat treatment process of Example 3-10 is a two-step method, the first step heat treatment temperature is 640°C, the time is 8 hours, the second step heat treatment temperature is 700°C, the time is 2 hours; the ion exchange process is the same as that of Example 1.
[0165] The heat treatment process of Examples 11-18 is a two-step process, wherein the first step heat treatment temperature is 640°C for 4 hours, and the second step heat treatment temperature is 680°C for 4 hours. The embodiment adopts a one-step ion exchange method, and the molten salt used is 80% NaNO 3 +20% KNO 3 Molten salt, ion exchange temperature is 480℃, and ion exchange time is 8h.
[0166] Comparative Example glass-ceramics were also prepared in the same manner as above. Comparative Examples 1-5 used two-step heat treatment during crystallization: the first step was at 640°C for 4 hours, and the second step was at 680°C for 4 hours.
[0167] Tables 1, 2 and 3 summarize the glass compositions and performance parameters of Examples 1 to 18 of the present application, and Table 4 summarizes the composition and performance parameters of the comparative glass. Figure 4-Figure 8 As shown, some performance tests of the comparative example are as follows Figure 9-10 As shown. Among them, Figure 4 is the XRD (X-Ray diffraction) spectrum of the glass-ceramics in Example 1 of the present invention; Figure 5 This is the transmittance curve of the glass-ceramics of Example 6 of the present application; Figure 6 , Figure 7 They are respectively a scanning electron microscope (SEM) image and a transmission electron microscope (TEM) image of the glass-ceramics of Example 6 of the present application; Figure 8 This is a stress curve diagram of ion exchange of glass-ceramics in Example 6 of the present application; Fig. 9 is the transmittance curve of the glass-ceramics of Comparative Example 1; Fig.10 The transmittance curve of the microcrystalline glass is analyzed for comparative example 4.
[0168] Among them, the XRD spectrum of the powdered microcrystalline glass sample can be measured by an X-ray diffractometer. The type of crystal phase in the microcrystalline glass can be determined by comparing the angle of the diffraction peak displayed on the XRD spectrum with the standard phase PDF card. Rietveld refinement of the XRD spectrum data can be performed to calculate the content of each crystal phase in the microcrystalline glass. The size of the crystal grains in the microcrystalline glass can be determined by SEM (Scanning Electron Microscope).
[0169] Among them, the optical properties of the glass, such as 550nm transmittance, haze, B value, etc., can be measured by using a UV-visible spectrophotometer on microcrystalline glass with a thickness of 0.7mm.
[0170] Among them, the Young's modulus of microcrystalline glass can be tested using an ultrasonic wave detector. Specifically, the glass sample is placed on the shear wave detector head of the ultrasonic material characterization system to collect shear wave signals, and then switched to the longitudinal wave detector head to collect longitudinal wave signals. The thickness and density of the test sample are input, and the Young's modulus value can be calculated through the calculation software in the system.
[0171] The Vickers hardness of glass can be calculated by dividing the load (N) when a diamond quadrangular pyramid indenter with a relative angle of 136° is pressed into a pyramid-shaped depression on the test surface of the glass sample by the surface area (mm 2 ) value; the test load is 0.1kgf and the holding time is 10 (seconds).
[0172] Among them, the stress properties of strengthened microcrystalline glass (such as DOL, CS_50, surface compressive stress, etc.) can be tested by a stress meter. Specifically, drop stress refraction liquid on the test path of the stress test equipment, then place the glass sample to be tested on the test path, input the thickness, refractive index, and photoelastic coefficient of the sample to be tested, and then click the start test button to obtain the relevant stress performance value.
[0173] Table 1
[0174]
[0175]
[0176] Table 2
[0177]
[0178] Table 3
[0179]
[0180]
[0181] Table 4
[0182]
[0183] From Table 1, Table 2 and Table 3, and Figures 4 to 8 The results show that, by reasonably adjusting the glass components and ratios, the present invention can obtain Mg-containing glass after heat treatment and crystallization. 2 SiO 4 Crystalline glass-ceramics, and the glass-ceramics can better take into account the characteristics of high transmittance, low coloration, high Young's modulus and high Vickers hardness, so as to better meet the application needs of glass-ceramics in electronic equipment and other fields.
[0184] by Figure 4 Taking the XRD spectrum of the glass-ceramics in Example 1 as an example, after the glass raw material is subjected to two-step heat treatment, obvious diffraction peaks appear in the glass-ceramics. 2 SiO 4 Compared with the standard PDF card, it can be seen that the diffraction peak is consistent with Mg 2 SiO 4The standard card is completely consistent with that of the present invention, which further proves that Mg does exist in the microcrystalline glass of the present invention. 2 SiO 4 Crystal. Figure 7 From the TEM photo of the glass-ceramics in Example 6, it can be seen that the interplanar spacing of the precipitated crystals is With Mg 2 SiO 4 The (200) crystal plane of the crystal is consistent, which further proves that the crystals precipitated in the glass are Mg 2 SiO 4 .
[0185] From the test results of Examples 1-18 in Table 1-3, it can be seen that the glass-ceramics of the present application example contains Mg 2 SiO 4 In the case of a crystal, it has a high transmittance in the visible light band, and its transmittance at 550nm is still greater than 88%, and the B value in the LAB three-dimensional color space is ≤0.5, and the optical performance is good. Figure 5 It can be seen from the transmittance curve of the glass-ceramics in Example 6 that the glass-ceramics has a high transmittance in the visible light band, and the transmittance at 550nm is specifically 90.3%, and there is no obvious absorption in the visible light band. There are two main reasons why the glass-ceramics in the embodiment of the present application has a high visible light transmittance: one is that the precipitated Mg 2 SiO 4 The crystal grain size is small (from Figure 6 It can be seen that the grain size of the microcrystalline glass is less than 100nm, which is much lower than the wavelength of visible light, and the scattering of visible light is small; secondly, the color of the microcrystalline glass is lighter, and the absorption of the visible light band is less. Under the combined effect, this application contains Mg 2 SiO 4 Crystalline glass-ceramics has a high transmittance.
[0186] It can be seen from the test results of Examples 1-18 in Tables 1-3 that the Young's modulus of the microcrystalline glass implemented in the present application is relatively high, ≥100 GPa; relative to the glass raw material, the Vickers hardness of the microcrystalline glass obtained after heat treatment is significantly improved, and the Vickers hardness of the microcrystalline glass after ion exchange is further improved.
[0187] From the test results of Examples 1-18 in Table 1-3, it can be seen that the glass-ceramics of the present application also have excellent ion exchange performance. After ion exchange, the surface compressive stress of the obtained strengthened glass-ceramics is ≥220MPa, the depth of the ion exchange layer (i.e., the strengthening layer) is greater than 100μm, and the compressive stress at a strengthening layer depth of 50μm is ≥100MPa. Figure 8 The stress curve of the glass-ceramics of Example 6 is shown as an example. Figure 8 It can be seen that the surface compressive stress of the microcrystalline glass after ion exchange reaches 271MPa, the depth of the ion exchange layer reaches 115μm, and the compressive stress at a depth of 50μm reaches 130MPa.
[0188] From Table 4 and Fig. 9 The test results of Comparative Example 1 show that when the SiO 2 When the molar content is too high (greater than 52%), the glass-ceramics becomes opaque and has a low transmittance, with the transmittance at 550nm being only 80.1%. The main reason may be that SiO 2 When the content is too high, the density of the glass network structure increases, resulting in Mg 2 SiO 4 The crystal particle size increases, which in turn affects the light transmittance.
[0189] From the test results of Comparative Example 2 in Table 4, it can be seen that when the alkali metal oxide in the glass component is only Li 2 O without Na 2 O.Ka 2 O、Cs 2 When one of the Li O phases is used, the transmittance of the glass-ceramic is low. The main reason is that the 2 O as alkali metal oxides can easily lead to poor glass forming properties, which is reflected in the glass melt being easily devitrified when it is cooled. In addition, since alkali metal oxides only have Li 2 O, the total amount of alkali metal ions in the system is low, Mg 2 SiO 4 The crystal particle size is relatively large during crystallization, which is not conducive to improving the transmittance of microcrystalline glass.
[0190] From the test results of Comparative Example 3 in Table 4, it can be seen that when the glass component contains Na 2 When the content of O is high, the transmittance of glass-ceramics is low. The main reason is that Na 2 Too high an O content can easily lead to phase separation of the glass during heat treatment, opacification of the glass, and reduced transmittance; and when a one-step ion exchange is used, the ion exchange performance is low. In addition, the total content of alkali metal oxides in Comparative Example 3 is high, which can also lead to reduced transmittance of the microcrystalline glass.
[0191] From Table 4 and Fig.10 The test results of Comparative Example 4 show that when the glass component contains TiO 2 When the content is too high, the transmittance of the microcrystalline glass is low, and its transmittance curve has obvious absorption in the visible light band. The main reason is that TiO 2 Too high a content will result in the Ti content in the glass-ceramics 3+ As the content increases, the absorption of visible light increases and the transmittance decreases.
[0192] It can be seen from the test results of Comparative Example 5 in Table 4 that when the MgO content in the glass component is too high, the transmittance of the microcrystalline glass is low. This is mainly because the increase in MgO content leads to a decrease in the stability of the glass, the glass is already opacified during the molding process, and the transmittance of the glass is reduced.
[0193] The above only expresses several exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which should be regarded as the scope of protection of the present application.
[0194] It should be understood that the first, second and various digital numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of this application. In this application, "greater than or equal to (≥)" and "less than or equal to (≤)" all include the number itself. The character " / " generally indicates that the objects associated with each other are in an "or" relationship. In this application, "and / or" is used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural.
[0195] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
Claims
1. A glass-ceramic, characterized in that: In terms of molar percentage, the microcrystalline glass comprises the following components: SiO2: 35%-52%; Al2O3: 5%-15%; Li2O: 2%-10%; Na2O: 0%-6%; K2O: 0%-15%; Cs2O: 0%-11%; MgO: 27%-38%; TiO2: 1%-6%; ZrO2: 0-4%; ZnO: 0-8%; CaO: 0-3%; BaO: 0-2%; GeO2: 0-5%; B2O3: 0%-6%; Among them, Na2O+K2O+Cs2O>0; the crystal phase in the microcrystalline glass includes forsterite crystal phase, and the microcrystalline glass is transparent in the visible light band.
2. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass does not contain Cr element.
3. The glass-ceramic according to claim 1 or 2, characterized in that: The crystalline phase in the glass-ceramics does not contain TiO2 crystals.
4. The glass-ceramic according to any one of claims 1 to 3, characterized in that: The molar percentage of Na2O is 0-2.9%.
5. The glass-ceramic according to any one of claims 1 to 4, characterized in that: The molar percentage of Cs2O is 0.1%-10%.
6. The glass-ceramic according to any one of claims 1 to 5, characterized in that: 5%≤Li2O+Na2O+K2O+Cs2O≤18%.
7. The glass-ceramic according to any one of claims 1 to 6, characterized in that: 0.4≤Al2O3 / (Li2O+Na2O+K2O+Cs2O)≤1.
4.
8. The glass-ceramic according to any one of claims 1 to 7, characterized in that: 0.5≤(MgO+Li2O+Na2O+K2O+Cs2O) / (SiO2+Al2O3)≤1.
2.
9. The glass-ceramic according to any one of claims 1 to 8, characterized in that: The molar percentage of MgO is 30.5%-38%.
10. The glass-ceramic according to any one of claims 1 to 9, characterized in that: The grain size of the forsterite crystal phase is less than or equal to 100 nm.
11. The glass-ceramic according to any one of claims 1 to 10, characterized in that: The microcrystalline glass also includes a clarifier, which includes one or more of Sb2O3, As2O3, SnO2, Na2SO4, K2SO4, Li2SO4, NaNO3, Ba(NO3)2, CaF2, and Na2SiF6.
12. The glass-ceramic according to any one of claims 1 to 11, characterized in that: When the thickness of the microcrystalline glass is ≤1 mm, the transmittance at a wavelength of 550 nm is ≥88%.
13. The glass-ceramic according to any one of claims 1 to 12, characterized in that: When the thickness of the microcrystalline glass is ≤1 mm, the haze in the visible light region is ≤0.2%.
14. The glass-ceramic according to any one of claims 1 to 13, characterized in that: When the thickness of the microcrystalline glass is ≤1 mm, the B value in the LAB three-dimensional color space satisfies: |B value|≤0.
8.
15. The glass-ceramic according to any one of claims 1 to 14, characterized in that: The Young's modulus of the microcrystalline glass is ≥100 GPa.
16. The glass-ceramic according to any one of claims 1 to 15, characterized in that: The Vickers hardness of the microcrystalline glass is ≥800kgf / mm 2 .
17. A method for preparing glass-ceramics, characterized in that: include: (1) Mixing raw materials corresponding to various components of the microcrystalline glass according to the component ratio of the microcrystalline glass, and obtaining glass raw materials after melting, forming, and annealing; wherein, in terms of molar percentage, the components of the microcrystalline glass include: SiO2: 35%-52%; Al2O3: 5%-15%; Li2O: 2%-10%; Na2O: 0%-6%; K2O: 0%-15%; Cs2O: 0%-11%; MgO: 27%-38%; TiO2: 1%-6%; ZrO2: 0-4%; ZnO: 0-8%; CaO: 0-3%; BaO: 0-2%; GeO2: 0-5%; B2O3: 0%-6%; Among them, Na2O+K2O+Cs2O>0; (2) heat-treating the glass raw material to crystallize the glass raw material to obtain microcrystalline glass; wherein the crystal phase in the microcrystalline glass includes a forsterite crystal phase, and the microcrystalline glass is transparent in the visible light band.
18. The preparation method according to claim 17, characterized in that: The heat treatment is a one-step heat treatment or a two-step heat treatment; when the heat treatment is a one-step heat treatment, the heat treatment temperature ranges from 640 to 900°C and the time is 2 to 20 hours; when the heat treatment is a two-step heat treatment, the first step heat treatment temperature is 600 to 660°C and the time is 0.5 to 10 hours; the second step heat treatment temperature is 660 to 900°C and the time is 1 to 20 hours.
19. A strengthened glass-ceramic, characterized in that: The strengthened microcrystalline glass comprises a main body layer and a strengthening layer located on the surface of the main body layer, and the main body layer comprises the microcrystalline glass described in any one of claims 1-16 or the microcrystalline glass prepared by the method for preparing microcrystalline glass described in any one of claims 17-18.
20. The tempered glass-ceramics according to claim 19, wherein: The depth of the strengthening layer is greater than or equal to 100 μm.
21. The tempered glass-ceramics according to claim 19 or 20, characterized in that: The surface compressive stress of the strengthened microcrystalline glass is greater than or equal to 220 MPa.
22. The strengthened glass-ceramics according to any one of claims 19 to 21, characterized in that: The compressive stress of the strengthened glass-ceramics at a depth of 50 μm in the strengthening layer is greater than or equal to 100 MPa.
23. The strengthened glass-ceramics according to any one of claims 19 to 22, characterized in that: The Vickers hardness of the strengthened microcrystalline glass is greater than or equal to 850 kgf / mm 2 .
24. A strengthened glass-ceramic, characterized in that: The strengthened microcrystalline glass is obtained by subjecting the microcrystalline glass described in any one of claims 1 to 16 to ion exchange.
25. A glass cover plate, characterized in that: The glass cover is made of the microcrystalline glass described in any one of claims 1-16, or is made of microcrystalline glass prepared by the method for preparing microcrystalline glass described in any one of claims 17-18, or is made of the strengthened microcrystalline glass described in any one of claims 19-23.
26. An electronic device, characterized in that: It includes a shell assembled on the outside of the electronic device and a circuit board located inside the shell, the shell is made of glass, and the glass includes the microcrystalline glass described in any one of claims 1-16, or the microcrystalline glass prepared by the method for preparing the microcrystalline glass described in any one of claims 17-18, or the strengthened microcrystalline glass described in any one of claims 19-23.
27. The electronic device according to claim 26, characterized in that The housing comprises a display screen cover plate assembled on the front side of the electronic device, and a back cover assembled on the back side of the electronic device; wherein the display screen cover plate and / or the back cover are made of the glass.
28. The electronic device according to any one of claims 26 to 27, characterized in that: The electronic device further comprises a camera assembly located inside the housing, the housing comprises a camera protection cover, the camera protection cover is covered on the camera assembly, and the camera protection cover is made of the glass.